An Expanded View of Joint Attention: Skill, Engagement, and Language in Typical Development and Autism. Issue 1 (9th October 2017) - Adamson, Lauren B.; Bakeman, Roger; Suma, Katharine; Robins, Diana L.
Abstract : This study provides an expanded view of joint attention and its relation to expressive language development. A total of 144 toddlers (40 typically developing, 58 with autism spectrum disorder [ASD], 46 with developmental delay [DD]) participated at 24 and 31 months. Toddlers who screened positive for ASD risk, especially those subsequently diagnosed with ASD, had poorer joint attention skills, joint engagement during parent–toddler interaction, and expressive language. Findings highlight the dynamic relation between joint attention and language development. In the ASD and DD groups, joint engagement predicted later expressive vocabulary, significantly more than predictions based on joint attention skills. Joint engagement was most severely impacted when toddlers did not talk initially and improved markedly if they subsequently began to speak.